2014
DOI: 10.1021/je500070k
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Density of Ternary Solution of Calcium Chloride + Sodium Chloride + Water from T = (293.15 to 323.15) K

Abstract: Viscosities and densities of ternary systems of CaCl 2 − NaCl−water were measured in the range of T = (293.15 to 323.15) K at 5 K intervals and up to 4.5 mol•kg −1 . Two equations based on the Exponential and Goldsack and Franchetto models were applied to correlate the experimental viscosity data as a function of concentration and temperature. The optimized parameters showed that the presence of CaCl 2 had a prevailing effect on the viscosity of the ternary solutions than NaCl. The dependency of the viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…(21) proposed by Kumar is accurate enough to predict the density of the ternary solution for the concentrations and temperatures range used in this study. This is true for the NaCl + CaCl 2 + H 2 O system as well 18 . conclusions Viscosity and density data for aqueous ternary system are still of interest for our industrial daily life applications.…”
Section: Goldsack Andmentioning
confidence: 79%
See 4 more Smart Citations
“…(21) proposed by Kumar is accurate enough to predict the density of the ternary solution for the concentrations and temperatures range used in this study. This is true for the NaCl + CaCl 2 + H 2 O system as well 18 . conclusions Viscosity and density data for aqueous ternary system are still of interest for our industrial daily life applications.…”
Section: Goldsack Andmentioning
confidence: 79%
“…In the previous work 18 , it has been shown that Eq. (3) failed to predict the corresponding viscosity of ternary solutions especially at higher concentrations.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations